Peer Group Support Change Perception Of Homeless And Beggar - Purwaningsih Purwaningsih; Eka Mishbahatul Mar’ah Has; Lailatun Ni’mah (Jurnal Ners, 2008)
Introduction: Homeless and beggar are social problem in our society. The reason of people who becomes homeless and beggar can be influenced by internal factors such as lazy to work, mental and physical illness. Meanwhile, it also can be influenced by external factors, such as economy, geography, social, education, pshycology, culture and religion. The aimed of this study was to analyze the effect of peer group support to perception about the homeless and beggar.Methods: A quasy experimental two group pre-post test purposive sampling design was used in this study. The subjects were homeless and beggar which stay at Lingkungan Pondok Sosial (Liponsos) Keputih-Surabaya for at least three day. There were 16 respondent who met to the inclusion criteria which divided into two group (controlled and treatment). Data were analyzed by using Wilcoxon Signed Rank Test and Mann Whitney U Test with significance level α≤0.05.Results: The result showed that controlled group has significance level p=0.109 and treatment group has significance level p=0.017, statistically by using Mann Whitney U Test showed p=0.021.Conclusion: It can be concluded that peer group support can change the perception about the homeless and beggar who stayed at Liponsos Surabaya. Peer group support can used continuously as social activity at Liponsos.